THE IMPACT OF CAPITAL INTENSITY ON FINANCIAL STABILITY OF ENERGY SECTOR COMPANIES IN INDONESIA - Muhammad Ramadhani Kesuma; Margareth Henrika S.; Lusiana Desy Ariswati (Journal of Financial Economics & Investment, 2025)
This study investigates the impact of capital intensity on the financial stability of energy sector companies in Indonesia from 2019 to 2023, using cash ratio and debt-to-equity ratio as stability indicators, while controlling for firm size and profitability (ROA). Employing a Random Effects Model on panel data from 40 publicly listed energy firms, the analysis reveals that capital intensity does not significantly affect financial stability. In contrast, profitability significantly enhances liquidity and reduces leverage, while firm size influences only solvency. These findings suggest that profitability is a stronger determinant of financial stability than capital intensity, particularly in the context of external volatility such as commodity price fluctuations. The study provides insights for energy firms to prioritize profitability to bolster financial resilience and recommends further exploration of external factors influencing sector dynamics.